Evaluation Of Some Pollinizers And Their Suitability On Productivity And Quality Of Walnut (Juglans Regia ) Cultivars (Applied Biological Research, 2016)
The present study was carried out at Horticultural Farm, Division of Fruit  Science, SKUAST, Shalimar, Srinagar (Kashmir) during 2012-13 to  evaluate various walnut pollinizers in improving the productivity and nut  quality. Pollen germination and its viability, pollen production rate, anther  and pollen morphology of ‘SKAU-W-0020’ and ‘SKUA-W-0022’ and  influence of pollination method i.e. open and cross on nut and kernel  characteristics was studied. Highest pollen viability (91.4%) was observed  in selection ‘SKAU-W-0020’. Maximum pollen germination (51.5%) was  observed in ‘SKAU-W-0020’ on medium containing agar agar powder  (1%) + sucrose (15%) + boric acid (100 ppm) + CaCl2 (1 mM). Pollen  production varied significantly within genotypes with maximum  (1,43,75000) in ‘SKAU-W-0020’ and minimum (1,20,60000) in ‘SKAU-W 0022’. Maximum anther length (2457 µm) and width (1228 µm) was in  ‘SKAU-W-0020’; however, maximum pollen length (35 µm) and width  (39.6 µm) was in ‘SKAU-W-0022’. Nut weight, diameter, length and kernel  length, weight and kernel percentage in ‘SKAU-W-0025’ and ‘SKAU-W 0015’ increased through cross pollination, however in ‘SKAU-W-0024’  and ‘SKAU-W-0008’ reverse trend was observed.
Keywords: Anther; germination; pollen; viability; walnut